Epidemiological and Clinical factors associated with mortality of confirmed Covid-19 cases admitted and treated in a tertiary care hospital of Patna, Bihar - Ranjan, Alok; Kumar, Sanjay; Singh, C M; Kumar, Pragya; Ayub, Arshad; Tiwari, Lokesh; Kumar, Sanjeev; Singh, P K (Indian Journal of Community Health, 2021)
Background: A significant proportion of the individuals having the illness of moderate to severe nature due to COVID-19 infection require immediate critical care. High incidence of mortality among elderly population or those with comorbid conditions were reported. Objectives: The study was carried out with objectives to assess the epidemiological and clinical factors associated with mortality among the COVID-19 cases admitted and treated in AIIMS, Patna. Methods: This was a hospital?based cross?sectional analytical study of epidemiological and clinical features of COVID?19?positive patients admitted and treated during the outbreak from March 20, to August 31, 2020. Results: The median age of COVID-19 cases was 51.5 years (IQR : 37-62 years) which was significantly higher (p-value = 0.001) as compared to females. Male-female ratio of cases was 2.88:1. Out of 1696 cases, the case-fatality rate was 309 (18.22%). The mean age of cases who died due to COVID-19 was significantly higher (p-value=0.001) as compared to those who survived. The odds of mortality was significantly higher in males as compared to females (Adjusted OR = 1.534, 95% CI = 1.10 – 2.13, p=0.011). The odds of mortality showed a significant increasing trend with increasing age (Mantel-Hanszel p-value for trend = 0.015). The covariates like gender, age groups 45-59, 60-74 and 75>=, breathlessness and CKD were found to be significantly associated with mortality after controlling for the confounders. Conclusions: Factors like gender, higher age, lower oxygen saturation causing breathlessness and chronic kidney diseases could be attributed to high risk of mortality in COVID-19 patients.